High-performance three-body near-field thermophotovoltaic energy conversion. (January 2021) - Dang, Chunzhuo; Liu, Xianglei; Xia, Haifeng; Wen, Shizheng; Xu, Qiao
Highlights: Energy transfer and conversion performance of a three-body near-field TPV system is studied. Traditional photonic crystals serving as filers may deteriorate performance in the near field. Inserting a thin metallic film can improve conversion efficiency from 24.7% to 35.3% at deep near-field. Output power can be further enhanced by 92.5% with the assistance of surface plasmon polaritons. Abstract: Three-body structures have shown great potentials in enhancing the heat transfer rate and tuning radiation spectrum in the near-field region, whereas are rarely considered in improving near-field radiative energy conversion performance. Here, a three-body thermophotovoltaic system configured by a tungsten emitter, a metallic spectrum control layer, and an In0.18 Sb0.82 Ga photovoltaic cell is considered. By parameter optimization of the spectrum control layer, the efficiency and output power at the gap distance of 10 nm are enhanced from 24.7% and 1.88×10 5 W/m 2 to 35.3% and 3.62×10 5 W/m 2, respectively. The potential mechanism lies in the excitation of coupled surface plasmon polaritons of the metallic spectrum control layer. This work paves the way for applications of three-body structure in thermophotovoltaic systems and designing high-performance energy conversion systems.